Translating Istanbul: Divergent Voices in Travel Writing - Gülmüş Sırkıntı, Halise (Text Matters: A Journal of Literature, Theory and Culture, 2025)
Intersemiotic research on urban discourse provides a dynamic perspective for interdisciplinary analysis, particularly within the context of Translation Studies. Drawing on Roland Barthes’s claim that the city is a “discourse” and Kevin Lynch’s notion that the image of the city is dynamic and influenced by the observer’s standpoint, in this study I examine three representations of Istanbul. Constantinople by Francis Marion Crawford, Letters from Constantinople by Georgina Adelaide Müller, and Constantinople: Old and New by H. G. Dwight are all treated here as examples of what Sündüz Öztürk Kasar terms traduction en filigrane (watermark translation). I also draw on Theo Hermans’s concept of “the translator’s voice” and adopt Bento’s categorization of tourist, traveler, and migrant travel writers to demonstrate how three distinct voices shape evolving interpretations of Istanbul through their authors’ unique experiences and backgrounds. Four recurring themes are identified across the travelogues: Galata as a site of cultural and social exchange, everyday life in Istanbul, the city’s mosques, and its cemeteries. Each translator leaves concrete “watermark” traces in their attempts to convey culturally embedded concepts to their audience; however, the extent and form of these traces vary depending on the translators’ level of cultural familiarity. This is particularly evident in Müller’s narrative, where the traces of traduction en filigrane are noticeably fewer; as a tourist translator with limited knowledge of the city and its traditions, she has fewer cultural elements to process and integrate into her text, which results in a more surface-level representation of Istanbul.